Integrating Augmented Reality and Ethnomathematics in Trinil Museum-Based Mathematics Education to Support Sustainable Development Goals - Pradnyo Wijayanti; Lisnani Lisnani; Heri Purnomo; Sumarni Sumarni; Ratu Mauladaniyati; Zidni Naufal Fadhil; Siti Muslikhatul Tsaniyah; Galuh Eko Nugroho; Gladys Sunzuma (Mathematics Education Journal, 2026)
Trinil Museum is one of the most important museums in Indonesia, with various historical collections related to ancient humans discovered by Eugene Dubois in the Trinil area, Ngawi, Indonesia. The objects in this museum are closely related to culture, history, and mathematical concepts. This study aims to develop an application in ethnomathematics tour media at the Trinil Museum based on augmented reality, integrating ethno-techno- realistic mathematics education to support SDGs that are valid, practical, and effective. This research employs an ethnographic approach, PMRI approach, and the ADDIE development model. Data was collected through questionnaires, interviews, tests, and documentation. The data analysis process used indicators of validity, practicality, and effectiveness. The results of this study developed an innovative ethnomathematics tour media for the Trinil Museum based on Augmented Reality that is valid, practical, and effective. This tour media is categorized as very valid, very practical, and effective. In these findings represent an innovation in mathematics education, both currently and in the future, namely the integration of ethno-techno-realistic mathematics education in the Trinil Museum ethnomathematics tour based on Augmented Reality to support SDGs 4 about quality of education.